A complete turnaround: police and gay men 1950–2010 - Williams, Clifford (Policing and society, 2025)
The remarkable turnaround within policing in England and Wales between 1950 and 2010 in relation to gay and bisexual men reflects both the change within society as well as legislation requiring equality and diversity. Change came about largely because the police service had to respond to changes outside their organisation, but latterly some change has been driven from within the organisation. The changes have enabled some gay and bisexual men to flourish within the police force and secure the confidence of people who in the past had good reason to fear the police. It has also given lesbian, gay, bisexual and trans people more confidence to report attacks on them. However, beneath the broad brush headlines, there is a complex history with many variations, particularly in the period 1950–1990. What may have happened in one police force, or even one police district, is not necessarily replicated in another force or area. Other than in North America, few detailed historical studies of police operating in this field have been published. Based on research into official archives, contemporary reports, first-hand accounts of retired police officers and examination of the reporting of cases, the author examines the changes over a sixty-year period in the way the police approached homosexuality both within society, as well as within the police service itself, thus providing a short history of this theme.